Ancient North Arabian (Safaitic) Inscriptions: Short messages from the Jordan Badia - Al-Manaser, A (University of Press, 2017)
The primary aim of this article is to present newly found ancient North Arabian inscriptions discovered in two locations within the Jordan Badia. This paper presents the first evidence that the “Safaic people/ Safaitic tribes” looked to the god Lt (Allat) as the queen of the earth. his article also tries to explain the meaning of the verb ʾṣḫ, which has been found in only a few inscriptions in Ancient North Arabian. The article concludes that the majority of verbs in Safaitic relate to sadness, grief, death, and worry and that we must translate inscriptions by understanding the meaning of the entire work and not just translate the component parts